Water Diplomacy: And the Share of the Nile River between Egypt, Ethiopia and Sudan - Kwesi Kyirewiah, Francis (Richtmann Publishing, 2022)
Water diplomacy across international borders can be a useful tool in solving problems related to the shared water resources of the political entities involved, especially when the interests of the countries are diverse. Water disputes can likely lead to potential conflicts if not properly address in a holistic manner to satisfy all parties concerned. Many discussions about water resources that cut across international borders have focused on their potential for either conflict or cooperation. Africa as a continent with shared resources is not isolated from these enormous challenges concerning the share of natural resources such as water. Africa is generally seen as a fragile region, and the signs of water conflicts in it have begun to appear in clear and dangerous forms. Diplomatic options for settling water disputes and avoiding any potential repercussions seems for the likelihood. Notwithstanding, these options Water Diplomacy has many challenges that limit its effectiveness owing to the deep political tensions among the countries. This study focused on analyzing the concept of water diplomacy and look into the dispute over the share of the Nile River, while highlighting the legitimate right of Egypt, Ethiopia, and Sudan in line with international conventions on water resources. Received: 24 September 2021 / Accepted: 25 November 2021 / Published: 5 January 2022